Circularly polarised magneto‐electric dipole antenna. Issue 14 (1st July 2014) - Liang, Weilong; Jiao, Yong‐Chang; Li, Jingwei; Ni, Tao
Abstract : A new design of a circularly polarised magneto‐electric dipole antenna is presented. The proposed antenna is composed of two magneto‐electric dipoles and a feeding network comprising a wideband 90° Schiffman phase shifter. The two magneto‐electric dipoles are cross‐placed. By using the proper feeding network, two orthogonal linearly polarised modes with a 90° phase difference for circular polarisation can be excited. Simulation results show that the 10 dB return loss bandwidth of the proposed antenna is 85.7% from 2 to 5 GHz, and the 3 dB axial ratio bandwidth is 61.5% from 2.7 to 5.1 GHz. The peak antenna gain is 8.3 dB. The measured results agree well with the simulation results.